If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10-2(a-1)=3+a
We simplify the equation to the form, which is simple to understand
10-2(a-1)=3+a
Reorder the terms in parentheses
10+(-2a+2)=3+a
Remove unnecessary parentheses
+10-2a+2=+3+a
We move all terms containing a to the left and all other terms to the right.
-2a-1a=+3-10-2
We simplify left and right side of the equation.
-3a=-9
We divide both sides of the equation by -3 to get a.
a=3
| 3x^2-8x-96=0 | | 2x+10=3x-40 | | 3x-6=-12 | | x^3+4x^2-60x=0 | | 18x^2-63x+10=0 | | 5x+3=12x | | h=3+17t-16t^2 | | 15-2n=6-1n | | 15-2n=6-q | | 2x+10+3x-40=180 | | 3x^2+18x-15=0 | | x^2+3x-60=0 | | (x+4)(x+4)=10 | | 5a-(7)+3a=17 | | 10x^2+7x-20=0 | | 1.5(b+6)+9=25 | | 2(z+5)+4=(-12) | | a^2+7a-9=0 | | 6g^2+g-2=0 | | 2x+3y+9=0 | | Y=-5x^2-2 | | x^2+3x^2=400 | | x^2+3x^2=20 | | 5n+3=2n-4 | | (-4)x+2-7x=15 | | 5x-8=7+5(x-3) | | -2x^2+4=4 | | 2*(-0.6)+9-7*(-0.6)=m | | (-4)*(-0.6)+2-7*(-0.6)=m | | (-4)*(-0.5)+2-7*(-0.5)=m | | 4(2b-1)=-76 | | 2*(-0.5)+9-7*(-0.5)=m |